2022
DOI: 10.3390/v14040712
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Pseudorabies Virus and Evaluation of Their Effects on Host Natural Immune Responses and Pathogenicity

Abstract: Pseudorabies, caused by the pseudorabies virus (PRV), is an acute fatal disease, which can infect rodents, mammals, and other livestock and wild animals across species. Recently, the emergence of PRV virulent isolates indicates a high risk of a variant PRV epidemic and the need for continuous surveillance. In this study, PRV-GD and PRV-JM, two fatal PRV variants, were isolated and their pathogenicity as well as their effects on host natural immune responses were assessed. PRV-GD and PRV-JM were genetically clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…All three groups of infected rats developed typical PR symptoms, such as itching, while histopathological analyses revealed varying degrees of pathological damage to several organs, including the brain, liver, and kidneys. These results are similar to those of studies by Zhou et al in mice [ 20 ]. A previous study [ 14 ] showed that PRV infection in mice affects their organs.…”
Section: Discussionsupporting
confidence: 93%
“…All three groups of infected rats developed typical PR symptoms, such as itching, while histopathological analyses revealed varying degrees of pathological damage to several organs, including the brain, liver, and kidneys. These results are similar to those of studies by Zhou et al in mice [ 20 ]. A previous study [ 14 ] showed that PRV infection in mice affects their organs.…”
Section: Discussionsupporting
confidence: 93%
“…The viral genome copies were detected in the brain, lungs, duodenum, jejunum, ileum, and colon of both the vaccination and vehicle groups. As mentioned earlier, the brain and lungs showed the highest viral loads in both groups (Zhou et al, 2022). Additionally, the colon exhibited the highest viral load among the intestinal tissues in both the vaccination and vehicle groups.…”
Section: Prv Xj Del Ge/gi/tk Protects Piglets Against Variant Prv Xj ...supporting
confidence: 71%
“…Due to the epitopes of gE protein localized at the aa positions 52-238 [43], the aa at position 54 (G→D) may be responsible for immune evasion. Previous studies showed novel PRV variants exhibited enhanced pathogenicity [35], and the variant strains HN1201, TJ, JS-2012 and hSD-1/2019 were more virulent and neurotropic to mice or pigs than the classical strains [13,17,44,45]. Whether the virulence of these isolates acquired in this study is enhanced remains to be further studied, involving proliferation characteristics in different types of macrophages, immune responses, pathogenicity to mice and pigs, etc.…”
Section: Discussionmentioning
confidence: 65%
“…The currently available vaccines only provide partial protection against virulent PRV infection. Recombination of PRV strains in Suidae may result in changes in antigenicity, virulence and thus immune failure, which could be the source of continuing epidemics in China [35]. PRV may have spread from domestic pigs to dogs, and then to wild boars, in which the virus established itself and continues to circulate [36,37], and PRV may also cause bovine death through interspecies infection [38].…”
Section: Discussionmentioning
confidence: 99%